Exploiting the 60 GHz band for local wireless multimedia access prospects and future directions. - Smulders, P. (IEEE Communications magazine)
This article addresses basic issues regarding the design and development of wireless access and wireless LAN systems that will operate in the 60 GHz band as part of the fourth-generation (4G) system. The 60 GHz band is of much interest since this is the band in which a massive amount of spectral space (5 GHz) has been allocated worldwide for dense wireless local communications. The article gives an overview of 60 GHz channel characteristics and puts them in their true perspective. In addition, we discuss how to achieve the exploitation of the abundant bandwidth resource for all kinds of short-range communications. The main tenor is that an overall system architecture should be worked out that provides industry with plenty of scope for product differentiation. This architecture should feature affordability, scalability, modularity, extendibility, and interoperability. In addition, user convenience and easy and efficient network deployment are important prerequisites for market success. This article discusses these features and indicates a number of key research topics